PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK LULUR MADU IBU SORAYA - Muhammad Syarif (Universitas muhammadiyah malang, 2016)
The purpose of this study is 1) to know the influence of product quality significantly to the purchasing decision 2) to know the influence of price significantly to the purchasing decision 3) to know the influence of of product quality and price simultaneously to the purchasing decision and 4) to know the variables that influence is dominant among the variables of product quality and price to the purchasing decision. The population of this research is the consumer who to do a purchase on product of Lulur Madu Ibu Soraya, Accidental Sampling technique definable then it can be as much as 100 research samples. Data analysis techniques used in this research is a method of multiple regression analysis. Based on the results of research and discussion by using multiple linear regression analysis that has been done then it can be drawn in summary as follows: 1) Quality product effect significantly to purchase decisions on product of Lulur Madu Ibu Soraya 2) Price effect significantly to purchase decisions on product of Lulur Madu Ibu Soraya. 3) Product quality and price take effect simultaneously to the purchasing decision on product of Lulur Madu Ibu Soraya 4) Product quality the dominant effect of the purchase decision on product of Lulur Madu Ibu Soraya.